AB0826 Hyperuricemic patients with systemic sclerosis do not present higher incidence of pulmonary hypertension but have worse echocardiographic parameters. (23rd January 2014) - Sarmiento, M.; Castellví, I.; Corica, M.E.; Diaz-Torne, C.; Geli, C.; Laiz, A.; Moya-Alvarado, P.; Rodriguez De la Serna, A.; Diaz-Lopez, C.; Casademont, J.; de Llobet, J.M.
Abstract : Background: Uric acid (UA) serum levels are increased in conditions that affect the oxidative metabolism. Several studies have demonstrated increased UA levels in patients with pulmonary hypertension (PH) and its relation to prognosis. There are few studies demonstrating the clinical significance of hyperuricemic in patients with PH secondary to systemic sclerosis (SSc). Objectives: To determine whether patients with SSc and PH have a higher frequency of hyperuricemica and to determine if there is greater frequency of PH in hyperuricemic and SSc patients. Methods: Retrospective review of cohort of patients with SSc from rheumatology unit of a tertiary university hospital. Hyperuricemia was considered if UA levels were higher than 6, 8 mg/dl and PH in either the presence of echocardiographic signs of PH or pulmonary artery pressure (PAP) >40mmHg. The following variables were collected: sex, age at diagnosis, type of SSc (limited, diffuse, earlySSc or without skin involvement), presence or absence of: digital ulcers (DU), sclerodermic renal crisis (SRC), interstitial lung disease (ILD), use of hyporuricemic therapy, colchicine and NSAIDs. Uric acid levels, renal and respiratory function parameters and echocardiographic parameters were recorded. To compare groups of qualitative variables chi-square or Fisher test were used, and T-test for quantitative variables. Statistical significance level was set to p values ≤0.05. Results: A total of 136 patients with SSc (93, 4% female, age at diagnosis 51, 02±15, 51 years) were included. Ninety five out of 136 presented limited SSc, 21 diffuse SSc, 19 early SSc and 1 sine scleroderma. One third (31, 6%) of the patients presented DU along their disease, 28, 7% ILD, 21, 3% PH and 2, 2% SRC. Patients with PH presented ILD more frequently (50% vs 23, 36% p =0.006), but the frequency of DU and SRC were not increased. Parameters of DLCO (Diffusing capacity for carbon monoxide)and FVC (Forced vital capacity) were significantly lower in patients with PH (56, 7±19, 1% vs 80, 13 vs 19, 13% and 77, 86±23, 42 vs. 95, 09±18, 3 p <0, 01). Higher ratio FVC/DLCO and thicker than the IVT (11, 52±3, 16 vs 10, 02±2, 18 p =0.03) were observed in these patients. No differences in the levels of UA in both groups were detected. Patients with hyperuricemia did not have higher frequency of PH (35, 7 vs 21, 5%, p ns) than those without, but they did show a higher frequency of SRC ( p <0.05). When comparing different echocardiographic parameters, patients with hyperuricemia had higher values of estimated PAP (45, 5±8, 081 vs 33, 41±9, 87 mmHg, p =0, 024), lower TAPSE (1, 6±0, 14 vs 2, 52±1, 78 cm, p =0, 01) and increased IVT thickness (12, 44±2, 78 vs 10, 25±2, 3 mm, p <0.05). Conclusions: Patients with PH had a higher ILD frequency. There was no difference in the frequency of hyperuricemia between groups. Hyperuricemic patients did not show a higher PH frequency, nevertheless they showed worse echocardiographic parameters. The presence hyperuricemia was also associated with higher frequency of SRC. Furthers works are needed to evaluate the effects of UA in SSc. Disclosure of Interest: None Declared